Group portrait of the attendees of the Epworth League Institute Conference in Lake Tahoe - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of attendees from various communities and churches throughout California, photographed at the Epworth League Institute Conference in Lake Tahoe.